A review of recent developments in rechargeable lithium–sulfur batteries. Issue 37 (9th September 2016) - Kang, Weimin; Deng, Nanping; Ju, Jingge; Li, Quanxiang; Wu, Dayong; Ma, Xiaomin; Li, Lei; Naebe, Minoo; Cheng, Bowen
Abstract : Various novel and nano-structured materials, and even outstanding structural designs, can achieve outstanding progress for lithium–sulfur battery systems. Abstract : The research and development of advanced energy-storage systems must meet a large number of requirements, including high energy density, natural abundance of the raw material, low cost and environmental friendliness, and particularly reasonable safety. As the demands of high-performance batteries are continuously increasing, with large-scale energy storage systems and electric mobility equipment, lithium–sulfur batteries have become an attractive candidate for the new generation of high-performance batteries due to their high theoretical capacity (1675 mA h g −1 ) and energy density (2600 Wh kg −1 ). However, rapid capacity attenuation with poor cycle and rate performances make the batteries far from ideal with respect to real commercial applications. Outstanding breakthroughs and achievements have been made to alleviate these problems in the past ten years. This paper presents an overview of recent advances in lithium–sulfur battery research. We cover the research and development to date on various components of lithium–sulfur batteries, including cathodes, binders, separators, electrolytes, anodes, collectors, and some novel cell configurations. The current trends in materials selection for batteries are reviewed and various choices of cathode, binder, electrolyte, separator, anode, and collector materials are discussed. The current challenges associated with the use of batteries and their materials selection are listed and future perspectives for this class of battery are also discussed.